Pemetaan Tren Riset dan Dampak Pedagogis Augmented Reality dalam Pembelajaran Fisika: Analisis Bibliometrik dan Systematic Literature Review - Fadilla, Fabrizia Hidayatul; Mumtaza, Aqilla; Fauzi, Ahmad; Afifi, Muhammad Wildan; Resbiantoro, Gaguk (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study comprehensively maps and analyzes the effectiveness and implementation challenges of Augmented Reality (AR) in Indonesian physics education from 2020 to 2024.Method – A combined bibliometric analysis and Systematic Literature Review (SLR) approach, following the PRISMA 2020 protocol, was used. One hundred (100) peer-reviewed articles from the Crossref database were collected. VOSviewer mapped publication trends, and SLR synthesized evidence across key indicators: learning outcomes, motivation, interest, critical thinking, and implementation barriers.Findings – Analysis of the 100 articles revealed five dominant research clusters: learning outcomes, motivation, interest, critical thinking, and implementation barriers. The SLR confirms substantial effectiveness of AR (average N-gain = 0.71, categorized as high) in improving students' conceptual understanding. However, its widespread integration faces persistent challenges related to digital infrastructure, technical reliability, curriculum alignment, and teacher readiness. Research Implications – To ensure sustainable integration, policymakers must prioritize strengthening digital infrastructure and teacher technical competence. The findings recommend that developers focus on creating AR content that is both pedagogically sound and designed for low-bandwidth environments to maximize the educational impact of AR in the Indonesian context.